2017
DOI: 10.1001/jamadermatol.2017.0201
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Age-Adjusted Population Analysis of Prevalence Estimates for Hidradenitis Suppurativa in the United States

Abstract: idradenitis suppurativa (HS) is a debilitating, painful chronic inflammatory disease for which the inherent unpredictability with respect to the course of disease and response to treatment poses significant challenges for patients. With sparse epidemiologic data for HS, disease burden has not yet been established. The prevalence of HS has been estimated using claims analyses, examinations, medical record reviews, or patient-administered questionnaires. Most prevalence studies have involved selected samples and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
286
6
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 304 publications
(316 citation statements)
references
References 19 publications
17
286
6
7
Order By: Relevance
“…Previous studies revealed a female preponderance for HS . In 2017, the large population‐based study of 47 690 HS patients in the USA showed that the incidence of HS was twice as high among women than men . In our study, there was no significant difference of the sex ratio in the HS patients, with an overall female : male ratio of 1.06:1.0.…”
Section: Discussioncontrasting
confidence: 48%
“…Previous studies revealed a female preponderance for HS . In 2017, the large population‐based study of 47 690 HS patients in the USA showed that the incidence of HS was twice as high among women than men . In our study, there was no significant difference of the sex ratio in the HS patients, with an overall female : male ratio of 1.06:1.0.…”
Section: Discussioncontrasting
confidence: 48%
“…Also, most experts concur that the maximum duration of the active form of HS in a given patient is about 20 years [6]. With regard to the estimated prevalence of the disease in European countries and in the United States, available data differ by up to four orders of magnitude, ranging from 0.00033% to 4.1% [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Situation In the Usa And Europementioning
confidence: 99%
“…Więk-szość ekspertów jest również zgodna, że czas trwania czynnej postaci HS wynosi u danego pacjenta maksymalnie ok. 20 lat [6]. Dane dotyczące częstości wystę-powania choroby w krajach europejskich i USA różnią się nawet o 4 rzędy wielkości i mieszczą się w przedziale od 0,00033% do 4,1% [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Sytuacja W Usa I Europieunclassified
See 2 more Smart Citations